Respon Apoptotik Dan Modulasi Ekspresi Gen BCL-2/p53 Pada Sel Kanker Payudara MCF-7 YANG Diinduksi Limfosit T CD8+ Autolog: Studi Ekspremental In Vitro - Qurratu Aini, Prisilia (Jurnal Biomedika dan Kesehatan, 2026)
Objective: Breast cancer remains the most prevalent malignancy among women in Indonesia, with 66,271 new cases annually and 70.9% diagnosed at advanced stages. The limitations of conventional therapies have driven the exploration of T cell-based immunotherapy as a promising alternative modality. This study aimed to evaluate the effectiveness of endogenous cytotoxic T cells from breast cancer patients in inducing MCF-7 cell line death in vitro without genetic or pharmacological modification. Methods: This quantitative analytical experimental study was conducted in vitro. Cytotoxic T cells were isolated from breast cancer patient PBMCs, activated with anti-CD3, and co-cultured with MCF-7 cells for 72 hours at Effector:Target ratios of 10:1, 20:1, and 50:1. Evaluation was performed using inverted microscopy (morphology), Annexin V-PI flow cytometry (viability/apoptosis), and qRT-PCR (BCL-2 and p53 expression). Statistical analysis employed ANOVA and Tukey's test (α=0.05). Results: T cell characterization showed CD3+/CD8+ population increase from 5.26% to >94% and NKG2D+ >98% post-activation. At 10:1 and 20:1 ratios, viability decreased minimally (86-87%) with apoptosis dominance (apoptosis:necrosis ratio 2.5:1). At 50:1 ratio, viability decreased dramatically (38.24%) but was dominated by necrosis (50%). BCL-2 expression decreased significantly across all treatments (p<0.0001): 56% (10:1), 51% (20:1), 20% (50:1). p53 expression showed massive downregulation of 96-99% across all ratios (p<0.0001), indicating a p53-independent cytotoxic mechanism. Conclusion: Endogenous cytotoxic T cells effectively induced MCF-7 cell death. Ratios of 10:1 and 20:1 produced programmed apoptosis with limited cytotoxicity, while 50:1 ratio achieved high killing efficacy but was dominated by non-specific necrosis. Exploration of intermediate ratios (30:1-40:1) is recommended for optimization. References : 56 (2015 – 2025)